Formas de N-orgânico em latossolo em função de nitrogênio e de plantas de cobertura em pré-safra do milho - Bergamasco, Marina Ali Mere [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The soil management in no-tillage system with cover crops and nitrogen levels changes the forms and the availability of N. A sensitive chemical index to detect variations in the availability of N caused by management can increase the accuracy of the fertilizer recommendations. With this work it was intended to evaluate the effects of cover crops in maize pre-cropping, and levels of N sidedress fertilization in maize, in the forms of soil organic N in a long-term experiment; to associate organic N forms with availability, through the correlation with N determined by direct steam distillation. The experiment is installed in a sandy clay Oxisol, in randomized blocks with split plots, with cover crops as main treatments and doses of N as secondary treatments. The cover crops are gray velvet bean, sunn hemp, jack bean, lablab, millet and spontaneous vegetation. The levels of urea-N sidedress fertilization in corn are 0 and 120 kg ha-1. The soil samples were collected in the twelfth year of the experiment, at the layers 0-5; 5-10; 10-20; 20-40; 40-60 cm, 30 days after the desiccation of cover crops. The samples were submitted to acid hydrolysis followed by the determination of: total hydrolysable N, hydrolysable NH4+-N, amino acids-N, amino sugars-N and acid insoluble-N. By subtraction were obtained unidentified-N (total hydrolysable-N - hydrolysable NH4+ + amino sugars + amino acids) and amino sugars-N (hydrolysable NH4+ + amino sugars - hydrolysable NH4+) .The amino sugars-N predominated over other hydrolysable-N fractions and cover crops had no clear effect on the definition of that dominance. Nitrogen fertilization decreased the N levels of the most labile fractions (hydrolysable NH4+ and amino sugars-N). There was a correlation between N determined by direct steam distillation and organic-N forms, particularly amino acids-N and amino sugars-N, which defined these fractions as organic N pools that controls the N availability

O manejo do solo em sistema plantio direto combinando plantas de cobertura e doses de nitrogênio pode interferir nas formas e na disponibilidade de N. Ter um índice químico sensível para detectar variações na disponibilidade de N causadas pelo manejo pode aumentar a precisão das recomendações. Pretendeu-se com este trabalho: avaliar os efeitos de plantas de cobertura em pré-safra de milho, e de doses de N em cobertura no milho, nas formas de N orgânico do solo, em experimento de longa duração; associar formas de N orgânico com disponibilidade, por meio de correlação com o N determinado por destilação a vapor direta. O experimento está instalado em Latossolo Vermelho argiloso, em blocos ao acaso com parcelas subdivididas, sendo as plantas de cobertura os tratamentos principais e as doses de N os tratamentos secundários. As plantas de cobertura são mucuna-cinza, crotalária, feijão-de-porco, lablab, milheto e vegetação espontânea e as doses de N-ureia em cobertura no milho são 0 e 120 kg ha-1. A amostragem de solo foi feita no décimo segundo ano do experimento, nas camadas de 0-5; 5-10; 10-20; 20-40; 40-60 cm de profundidade, 30 dias após a dessecação das plantas de cobertura. As amostras foram submetidas à hidrólise ácida e as formas do N orgânico determinadas no fracionamento foram: N-total hidrolisável, N-NH4+ hidrolisável, N-aminoácidos, N-NH4+ hidrolisável + N-aminoaçúcares e N-insolúvel em ácido. Por diferença foram obtidos os teores de N-não identificado (N-total hidrolisável - N-NH4+ hidrolisável + N-aminoaçúcares + N-aminoácidos) e de N-aminoaçúcares (N-NH4+ hidrolisável + N-aminoaçúcares - N-NH4+ hidrolisável). A fração N-aminoaçúcares predominou em relação às outras formas de N-hidrolisável e o cultivo de plantas de cobertura não teve efeito claro na definição desse predomínio. A adubação nitrogenada diminuiu os teores de N das frações mais lábeis...
Keywords: Gramínea; Leguminosa; Adubação; Fertilizantes nitrogenados; Nitrogenio na agricultura; Nitrogen fertilizers